(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article explores the genre transformations in the short prose of Charles Dickens, focusing on the artistic features of the sketch-story genre in Sketches by Boz. The study analyzes Dickens’s combination of realism, journalism, satire, and social criticism in depicting Victorian London and its lower classes. Particular attention is paid to documentary detail, atmosphere, open endings, and moral issues in Dickens’s early prose. The article concludes that Dickens’s sketch-stories are not only preparatory works for his novels but also an important contribution to the development of nineteenth-century English short prose.